Macrolichen Communities Depend on Phorophyte in Conguillío National Park, Chile - Johana Villagra; Leopoldo G. Sancho; David Alors (Plants, 2023)
The community composition of epiphytic macrolichens from two tree species (Araucaria araucana and Nothofagus antarctica) was conducted in temperate forests in the Conguillío National Park, Chile. The composition of lichen biota is influenced by phorophyte species, bark pH, and microclimatic conditions. A total of 31 species of macrolichens were found on A. araucana and N. antarctica. Most of the species showed phorophyte preference, with nine being exclusive to A. araucana and 10 to N. antarctica. The detrended correspondence analysis (DCA) indicated the formation of three communities: one representing macrolichens growing on N. antarctica and two others growing chiefly on A. araucana, either with north or south exposure. More work is needed to study the lichen biota of the forests of the Chilean Andes, which are under multiple threats, including clearing and climate change. In order to counteract such risks to native forests and to the biodiversity of the associated epiphytic lichens, conservation plans should be established that consider the factors that influence the composition of the lichen community.